Theoretical and experimental studies on tapered plate-rubber isolator. (October 2020) - He, Wenfu; Zeng, Yifeng; Wang, Changhong; Liu, Wenguang; Xu, Hao; Keleta, Yonas
Abstract: Earthquake is one of the biggest threats for multi-story buildings in the developing countries. Thus, a cost-effective base isolation bearing is designed to overcome the challenge. Tapered plate-rubber isolator consists of a set of cover plates and a detached rubber interlayer, which can balance seismic isolation and economic expenditure. Theoretical and experimental studies will focus on the hysteretic behaviors. Energy consumption of three design parameters is discussed, including the slope of the tapered plane surface, elasticity and thickness of the rubber sheet. Effective stiffness and damping ratio are derived by the hysteretic energy dissipation curves, and finally shaking table test is set up to evaluate the structural reaction. Results indicate that tapered plate-rubber isolator can dissipate seismic energy efficiently, which will minimize the dynamic responses of the superstructure. Low-cost, easy manufacture and high earthquake energy dissipation will support it to be an efficient isolation bearing for the multi-story buildings.